Enhancing Early Childhood Teachers’ Creativity through the Implementation of the Merdeka Curriculum: An Experimental Study in Surakarta - Wahyuningsih, Siti; Rasmani, Upik Elok Endang; Winarji, Bambang; Nurjanah, Novita Eka; Jumiatmoko; Fitrianingtyas, Anjar; Zuhro, Nurul Shofiatin (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
Creativity is a crucial skill for early childhood education (ECE) teachers in fostering innovative and adaptive learning environments. The Merdeka Curriculum (Independent Curriculum) in Indonesia provides teachers with the flexibility to design and implement innovative teaching strategies tailored to students’ needs. This study examines the impact of the Merdeka Curriculum on ECE teachers’ creativity using a quantitative experimental method with a One-Group Pretest-Posttest Design. A total of 100 ECE teachers in Surakarta participated in this study. Creativity was assessed before and after three months of curriculum implementation. The results showed a significant increase in teachers’ creativity scores from 49.80 (pretest) to 89.55 (posttest). A paired-samples t-test confirmed a statistically significant difference (p < 0.001), and the N-Gain score analysis indicated a high level of effectiveness (0.78). These findings suggest that the Merdeka Curriculum fosters teacher creativity by allowing greater autonomy in instructional design and innovative pedagogical practices. However, challenges such as limited professional training and inadequate resources hinder optimal curriculum implementation. This study contributes to the existing literature on teacher creativity by demonstrating the effectiveness of curriculum flexibility in enhancing instructional innovation. Future research should explore the long-term impacts across different regions and examine policy interventions that support sustainable teacher development in ECE settings.